2015
DOI: 10.1186/s13567-015-0248-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterisation of microsatellite DNA markers in order to recognise the WSSV susceptible populations of marine giant black tiger shrimp, Penaeus monodon

Abstract: White spot disease (WSD) which is caused by white spot syndrome virus (WSSV) creates severe epizootics in captured and cultured black tiger shrimp, resulting a huge loss in the economic output of the aquaculture industry worldwide. Performing selective breeding using DNA markers would prove to be a potential cost effective strategy for long term disease control in shrimps. In the present investigation, microsatellite DNA fingerprints were compared between naturally occurring WSSV resistant and susceptible popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…For instance, all nine data sets reported in one study (Laramore et al., ) were carried out with different cohorts of shrimp. There can be large differences in host susceptibility to a pathogen (Ben‐Ami, Ebert, & Regoes, ; Chakrabarty, Dutta, Mallik, Mondal, & Mandal, ) and for insects susceptibility can be phenotypically plastic and linked to environmental factors such as host density (Reeson, Wilson, Gunn, Hails, & Goulson, ). Although we cannot rule out antagonistic dose‐dependent action, we therefore think that the most likely explanation for deviations from IAH model predictions is differences in the distribution of host susceptibility to WSSV.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, all nine data sets reported in one study (Laramore et al., ) were carried out with different cohorts of shrimp. There can be large differences in host susceptibility to a pathogen (Ben‐Ami, Ebert, & Regoes, ; Chakrabarty, Dutta, Mallik, Mondal, & Mandal, ) and for insects susceptibility can be phenotypically plastic and linked to environmental factors such as host density (Reeson, Wilson, Gunn, Hails, & Goulson, ). Although we cannot rule out antagonistic dose‐dependent action, we therefore think that the most likely explanation for deviations from IAH model predictions is differences in the distribution of host susceptibility to WSSV.…”
Section: Discussionmentioning
confidence: 99%
“…The WOAH‐certified kits are being widely used by many researchers, worldwide 52–54 . However, it seems that the other diagnostic kits are not commonly used in scientific studies, except for the single‐tube WSSV detection kit (GeNei, India), which has been cited in a few research articles and has a detection limit of 10 viral particles per reaction, with detection times ranging from ~3.5 to 4 h 55–57 …”
Section: Molecular Diagnostic Methods For Shrimp Viral Diseasesmentioning
confidence: 99%
“…Most are based on nested and real‐time PCR methods, and the LOD of the majority of kits is approximately 10 copies (Table S2). Only a few kits have been used in scientific research, 55,89,90 such as the IQ2000™ IHHNV DPS kit (GeneReach), which has a detection limit of ~10 copies/reaction, and the time from sample preparation to final results is ~3.5 to 4 h. Previously, Tang et al 71 reported that the IQ2000™ IHHNV DPS kit reacted with the non‐infectious IHHNV type, which could lead to misdiagnosis. Since then, the developers have improved the kit, which could specifically amplify the infectious types, but not non‐infectious IHHNV.…”
Section: Molecular Diagnostic Methods For Shrimp Viral Diseasesmentioning
confidence: 99%
“…85,86 Genetic variation associated with increased pathogen resistance and tolerance has been identified and targeted in studies for application in selective breeding programs to yield more robust production stocks. 32,85,[87][88][89][90][91] In the context of disease resistance, such genetic variation resulting in stock improvement can be slight. For example, a single nucleotide polymorphism (SNP) (g.1186A > G) in the anti-lipopolysaccharide factor 3 (ALFPm3) gene of P. monodon has been associated with higher rates of survival during WSSV challenge.…”
Section: Sourcementioning
confidence: 99%